PELATIHAN KETERAMPILAN BERBAHASA JEPANG MELALUI METODE BERMAIN PERAN - Ni Luh Gede, Meilantari,; Kadek Febriana , Theresia, (LOKATARA SARASWATI, 2024)
Japanese is a foreign language that have been included in Indonesian school curriculum for many years. The Specified Skill Worker (SSW) visa program of the Japanese government permits graduates of vocational schools to work in Japan. As a result, there is a need to keep improving Japanese language instruction, particularly at vocational institutions. SMK Saraswati 3 Denpasar is one among the schools that offers Japanese lessons. Saraswati 3 Vocational School Denpasar is fully aware of the importance of foreign language proficiency for students, particularly those in class XII. The issue was that the Japanese language class was only taught once a week for two lesson hours (2 JP), which was not ideal when the service team conducted initial observations and interviews with subject teachers. Meanwhile, Japanese is a challenging language to master because it has three types of letters. To address the issue of a lack of Japanese language subject hours and develop students' speaking skills, the social service team employs the role-playing method. This is done since this strategy is relatively new to students